Gilbert Thompson journal - Thompson, Gilbert, 1839-1909.
Journal (1861-1864) of Thompson's Civil War experiences in Maryland, Virginia, and Washington, D.C., while serving as a topographical engineer in the Engineer Battalion, U.S. Army of the Potomac. Includes later reminiscences; description of bridges, armaments, and firearms; and sketches and photographs of army officers, battle sites, etc. Includes correspondence, laid in, of Nathaniel Prentiss Banks.
Union soldier and topographical engineer.
Collection material in English.
List of illustrations available in the Library of Congress Manuscript Reading Room.
Keywords: Banks, Nathaniel Prentiss, -- 1816-1894 -- Correspondence; United States. -- Army -- Officers; United States. -- Army of the Potomac. -- Engineer Battalion; Bridges; Military weapons; Maryland -- History -- Civil War, 1861-1865.; United States -- History -- Civil War, 1861-1865 -- Battlefields; United States -- History -- Civil War, 1861-1865 -- Engineering and construction; Virginia -- History -- Civil War, 1861-1865.; Washington (D.C.) -- History -- Civil War, 1861-1865.; Engineers; Soldiers